Do Students Need Multimedia Based Grammar 3 Teaching Material? - Fitrawati, Fitrawati; Oktavia, Witri (English Department FBS UNP, 2017)
This article presents a part of a study conducted to develop multimedia based teaching material for Grammar 3. It aims at describing needs and problems of students in learning Grammar 3 through a descriptive study. The data were gathered from the questionnaires distributed to the students who have taken Grammar 3 course. The result of the research conveys that 1) there is a gap between the objective of Grammar 3 course and the studentsâ€™ achievement in the class, 2) students get the problems in understanding Grammar 3 due to inappropriate teaching materials used in teaching and learning process, and 3) the students need a multimedia based teaching materials to improve their understanding and achievement in Grammar 3 course.Key words/phrases:teaching material development, multimedia, need analysis, Grammar 3Â APAKAH MAHASISWA MEMBUTUHKAN MATERI AJAR GRAMMAR 3 BERBASIS MULTIMEDIA?AbstrakArtikel ini merupakan salah satu bagian dari rangkaian penelitian pengembangan materi ajar Grammar 3 berbasis multimedia. Penelitian deskrptif ini bertujuan untuk mendeskripsikan masalah dan kebutuhan mahasiswa terhadap materi Grammar 3. Oleh karena itu, data dikumpulkan melalui kuesioner yang disebar kepada seluruh mahasiswa yang telah mengambil mata kuliah Grammar 3. Hasil penelitian menunjukan bahwa 1) adanya ketimpangan antara tujuan pembelajaran Grammar 3 dan kemampuan yang dikuasai mahasiswa; 2) mahasiswa mengalami kesulitan dalam memahami materi Grammar 3 karena kurang memadainya materi yang digunakan dalam proses belajar dan mengajar; dan 3) mahasiswa membutuhkan materi ajar berbasis multimedia yang dapat membantu meningkatkan pemahaman dan kemampuan mereka pada materi Grammar 3.Kata Kunci/frase: pengembangan materi ajar, multimedia, analisis kebutuhan, Grammar 3